Technology tools for today's high-margin practice : how client-centered financial advisors can cut paperwork, overhead, and wasted hours - Drucker, David J., 1948-; Bruckenstein, Joel P., 1956- (Hoboken, N.J. : Bloomerg Press, An Imprint of Wiley, 2013)
Your financial advisory practice with the latest cutting-edge toolsTired of spending more time with filing cabinets than with clients' Is overhead eating up your margins' In a new revised edition of the "bible" of practice management and technology for financial professionals, two leading financial planners, with some help from their friends*, deliver the knowledge advisors have been begging for. This book serves up a nontechnical trove of technology, clever workarounds, and procedural efficiencies tailored to help financial advisors in private practice move toward today's virtual office. The authors show you how to drastically reduce the paperwork in your office, slash overhead, and find anything you need in seconds using the latest software. This revised edition includes new information on SaaS and cloud computing, software integrations, mobile devices/apps, social media tools, portfolio accounting and outsourcing, collaborative tools, digital signatures, workflow management, marketing technology and much more. Perfect for successful practices seeking greater efficiencies and healthier profit marginsThe authors are well-known financial advisors, each with more than 30 years of experience in financial servicesAddresses the evolution of the virtual office and its impact on advisory firms If you're looking for new systems and efficiencies to transform and streamline your private practice, look no further than Technology Tools for Today's High-Margin Practice. *Chapter 1 Selecting the Right CRM System, Davis D. JanowskiChapter 2 The Future of Financial Planning Software, Bob CurtisChapter 3 The Future of Financial Planning Software and the New Client-Advisor Relationship, Linda StrachanChapter 4 Portfolio Management Software, Mike KellyChapter 5 Achieving Growth and Profitability with Technology Integration, Jon PatulloChapter 6 How the World Wide Web Impacts the Financial Advisor, Bart WisniowskiChapter 7 Managing Your Online Presence, Marie SwiftChapter 8 Client Portals and Collaboration, Bill WinterbergChapter 9 The Cloud, J.D. BruceChapter 10 Digital Signature Technology, Dan SkilesChapter 11 Innovative Software and Technologies Implemented at One of the United States' Leading Advisory Firms, Louis P. StanasolovichChapter 12 Virtual Staff Sparks Growth, Profitability, and Scalability, Jennifer GoldmanChapter 13 ROI-The Holy Grail of the Technology Purchase Decision, Timothy D. WelshChapter 14 Building an Efficient Workflow Management System, David L. Lawrence</p.
Includes index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Financial planners; Finance, Personal -- Computer network resources; Investment advisors; Investments -- Data processing; Finance -- Technological innovations; Planificateurs financiers; Conseillers en placements; Investissements -- Informatique; Finances -- Innovations; investment counsels; BUSINESS & ECONOMICS -- Investments & Securities -- General; Finance, Personal -- Computer network resources; Finance -- Technological innovations; Financial planners; Investment advisors; Investments -- Data processing